Estimação bayesiana para medidas de desempenho de testes diagnósticos - Pinho, Eloísa Moralles do (Universidade Federal de São Carlos, 2006)
In the medical area, diagnostic tests are used to classify a patient as positive or negative with respect to a given disease. There are simple and more elaborate tests, each one with a speci9ed rate of misclassi9cation. To verify the accuracy of the medical tests, we could have comparisons with a "gold stantard", here is a test with no error. In many situations we could not have "gold standard", by ethical reasons or by chance that the individual is disease free or by high costs of the test. Joseph et al (1999) introduces a Bayesian approach that solves the lack of a gold standard, by using latent variables. In this work, we introduce this Bayesian methodology giving generalizations in the presence of covariates. A comparative study is made with the presence or not of gold standard to check the accuracy of the medical tests. Some diGerent proportions of patients without gold standard are considered in a simulation study. Numerical examples are considered using the proposed methodology. We conclude the dissertation assuming dependence among two or more tests.
Keywords: Teoria bayesiana de decisão estatística; Especificidade a posteriori; Sensibilidade a posteriori; MCMC; Testes diagnósticos; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA